Tensile Properties of Pandanus Atrocarpus based Composites - Hoo Tien, Nicholas Kuan; Meng, Chuen Lee (JASPE, 2014)
Pandanus atrocarpus, or locally known as mengkuang plant is likely to be potential natural fibre reinforcement in composite. Both the Pandanus leaves, and fibres extracted from the Pandanus leaves were used in composite fabrication. Fibres were extracted from Pandanus leaves with water retting process. Pandanus composites were laminated using compression moulding method. The tensile properties of composite laminates based on lamination of Pandanus leaf- and extracted Pandanus fibre-reinforced polyethylene were investigated. Tensile tests have shown that composite laminates based on extracted Pandanus fibre reinforced polyethylene were more superior than using the Pandanus leaf itself without extracting its fibre. Tests exhibited that increasing the volume fraction of Pandanus fibre resulted in strength increase. This suggests that Pandanus fibre- based composites could offer a range of mechanical properties for use in the engineering industry.